PELAKSANAAN GANTI RUGI KECELAKAAN KERJA YANG MENGAKIBATKAN CACAT SEBAGIAN UNTUK SELAMANYA PADA PT. SARI HUSADA Tbk. - , ANDRI WIBOWO; , Dr. Ari Hernawan, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Abstract of research is aimed to determine the Provision of Social Security especially employment accident insurance benefit and explains implementation on the payment of compensation by PT. Sari Husada, Tbk to worker who suffers occupational accident which led to the partially disable forever. This research is qualitative research is a research procedure that yields descriptive of work written or spoken an the observed behavior. Engineering research is a affcation descriptive inductive, with an interview a way collecting the data. Data sources include primary law, material law secondary, and in the material legal tertiary. Data analysis was done with interpretation of legal legislative regulations, to derive conclusions and answer in the formulation of the problems. So this research can know how big responbility and liability of PT. Sari Husada Tbk against workers had partially disabled to work forever because of accident, at is Regulation in Government of the Republic of Indonesia Number 14 by 1993 on the Implementation of Social Security Program Labor (including all the change were to the chang nine is Regulation in Government of the Republic of Indonesia Number 83 by 2013). As well as based related legislation is particulary on labor Social Security.